Starptautiskā konference "Jauno vēsturnieku zinātniskie lasījumi X": konferences referātu tēzes, Valmieras muzejs, 2024. gada 28.–29. novembris - Bikše, Ginta Ieva (My University, 2024)
Starptautisko konferenci “Jauno vēsturnieku zinātniskie lasījumi X” 2024. gada 28.–29. novembrī rīko LU Humanitāro zinātņu fakultātes Latvijas vēstures institūts un Valmieras muzejs, sadarbībā ar Vītauta Dižā Universitāti Kauņā, Lietuvas Vēstures institūtu un Tartu Universitātes Vēstures un arheoloģijas institūtu. Starpdisciplinārā konference norisinās jau desmito gadu, šogad piesaistot 35 Latvijas, Lietuvas, Igaunijas un Francijas jaunos vēsturniekus, kuri dominējoši aplūko dažādus 20. gadsimta Baltijas reģiona, Eiropas un arī Āzijas vēstures aspektus, tomēr vairāki referenti koncentrējas uz aizvēstures, viduslaiku un jauno laiku tematiku
International Conference “Scholarly Readings of Young Historians X” : ABSTRACTS, Valmiera Museum, 28–29 November 2024
The Scholarly Readings of Young Historians X will be held on 28–29 November 2024, by the Institute of Latvian History of the Faculty of Humanities, University of Latvia, and Valmiera Museum, in co-operation with Vytautas Magnus University in Kaunas, the Lithuanian History Institute, and the Institute of History and Archaeology of Tartu University. During the 10th year of the interdisciplinary conference, 35 young historians from Latvia, Lithuania, Estonia, and France will present their research, predominantly focusing on various aspects of the history of the Baltic region, Europe, and Asia in the 20th century, however, several presenters will also look at the topics of prehistory, the Middle Ages, and Early Modern Period.
Keywords: 20. gadsimta vēsture; Arheoloģija; Militārā vēsture; drukātā prese Latvijā; Valmieras vēsture; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects; Inflantians; Relations, Latvia - the Soviet Russia; Restoration of Estonia’s Independence; Boxer Rebellion in China; Governor-General of Indochina Jules Brévié; Spanish Civil War in Periodicals; Medieval Livonian Towns; Floral Motifs in the Tile Decor; Shrove Tuesday Carnival; Midwives in Dorpat University; Life Stories of Estonian Wome; Gustavs Tūrs; Bronze Age Landscape in Lubāns Plain; Archaeological Research of Ceramic Vessels - Valmiera; Russification Policy; Central Criminal Police Criminal Department; Defence of the Interests of Civil Employees; Prosecutor’s Office in Latvia (1918–1940); Swedish Army in Vidzeme; Genealogy; Census Data of 1935; Aizsargi; Latvian Armed Forces; Latvian Art History; Latgale; “Laikmets”, “Latvju Mēnešraksts”; Viesīte